DYNAMICS C-REACTIVE PROTEIN AND CERULOPLASMIN IN THE BLOOD OF PATIENTS WITH COMBINED THORACIC TRAUMA AS A PROGNOSTIC CRITERION OF TRAUMATIC DISEASE (World Science, 2021)
Purpose: to assess the informativeness of the level of "acute phase" proteins in the blood and their changes in the acute and early period of traumatic disease in patients with combined thoracic trauma with polytrauma as a marker of disease severity and the impact of proposed modifications of intensive care algorithm on treatment results.Material and methods. The basis of this study is a statistical analysis of the results of a comprehensive examination of 92 patients with thoracic trauma. Control points were 1st, 2nd, 3rd, 5th,7th and 12th  day of treatment. The severity of the injury was determined according to the ISS scale, the condition of patients at the time of admission according to the ARASNE II scale, the level of C-reactive protein and ceruloplasmin in the blood. 3 groups of patients were identified. Group I - standard IT protocol, group II - standard IT protocol with the addition of ceruloplasmin, group III - standard IT protocol with the addition of a solution of D-fructose-1,6-diphosphate sodium salt of hydrate. Parametric statistics methods were used to process the obtained data.Results. In patients with combined thoracic trauma, it is important when planning the patient's management tactics to diagnose the content of  CRP and CP in the blood during the entire period of stay in the intensive care unit.  The level of CP in the blood of patients with combined thoracic trauma is a highly informative diagnostic marker of the impact of hypoxia of mixed genesis on the course of traumatic disease in general. The leading mechanism for the development of acute lung injury syndrome in patients with combined thoracic trauma is oxidative stress, so the appointment of ceruloplasmin as an adjunct to the standard protocol of intensive care is pathogenetically justified.Conclusions. In patients with combined thoracic trauma, it is important when planning patient management tactics to diagnose the content of C-reactive protein and ceruloplasmin  in the blood during the entire period of stay in the intensive care unit. The level C-reactive protein and ceruloplasmin  in the blood of patients with combined thoracic trauma is a highly informative diagnostic marker of the prognosis. There is oxidative stress, so the appointment of ceruloplasmin as an adjunct to the standard protocol of intensive care is pathogenetically justified.